Human capital, gender, institutional environment and research funding: Determinants of research productivity in German psychology. - Martin Schröder; Isabel M Habicht; Mark Lutter (PLoS ONE)
Which academics are more productive? The "sacred spark" theory predicts that some researchers are innately more productive than others, while the theory of cumulative advantage argues that small initial inequalities accumulate to large differences in productivity over time. Using a virtually complete panel dataset of all academic psychologists found in German universities in 2019, including their career information and publications, we examine under what conditions male and female psychologists publish more peer-reviewed articles. The strongest predictor of this is prior experience in publishing peer reviewed journal articles, irrespective of other prior endowments. This relationship between earlier and later productivity is not strongly confounded by career stage, affiliation with elite institutions, receipt of third-party funding, or parenthood. The effect of prior publications on current productivity explains why female academic psychologists publish less than men do. While female psychologists publish 34% less than their male counterparts, this gap diminishes to 17% after controlling for prior publication experience. This lends supports to the theory of cumulative advantage, which explains overall differences in productivity over entire careers by the accumulation of minor initial inequalities to large outcome differences over time.